2020
DOI: 10.1186/s12887-020-2019-0
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of mutations in KIF7 and KIAA0556 in Joubert syndrome with ocular coloboma, pituitary malformation and growth hormone deficiency: a case report and literature review

Abstract: Background: Joubert syndrome is a recessive neurodevelopmental disorder characterized by clinical and genetic heterogeneity. Clinical hallmarks include hypotonia, ataxia, facial dysmorphism, abnormal eye movement, irregular breathing pattern cognitive impairment and, the molar tooth sign is the pathognomonic midbrain-hindbrain malformation on magnetic resonance imaging. The disorder is predominantly caused by biallelic mutations in more than 30 genes encoding proteins with a pivotal role in morphology and func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 26 publications
0
19
0
1
Order By: Relevance
“…Conditional ablation of Bbs5 at both juvenile and adult stages does not appear to result in enlarged ventricles.In summary, the Bbs5 mutant mouse described here will be a good model to evaluate multiple phenotypes associated with BBS patients. Importantly, this includes pituitary defects.Pituitary abnormalities have been reported in both BBS and Joubert Syndrome (JBTS; OMIM 213300) patients(35,39). This study is the first to show defects in pituitary development in a BBS mouse model.…”
mentioning
confidence: 63%
“…Conditional ablation of Bbs5 at both juvenile and adult stages does not appear to result in enlarged ventricles.In summary, the Bbs5 mutant mouse described here will be a good model to evaluate multiple phenotypes associated with BBS patients. Importantly, this includes pituitary defects.Pituitary abnormalities have been reported in both BBS and Joubert Syndrome (JBTS; OMIM 213300) patients(35,39). This study is the first to show defects in pituitary development in a BBS mouse model.…”
mentioning
confidence: 63%
“…Whilst there remain very few studies of Katnip function, it has a growing association with human disease. In addition to several studies finding Katnip mutations in patients with Joubert's syndrome (Cauley et al, 2019;Niceta et al, 2020;Sanders et al, 2015), reduced expression was also found to be associated with Alzheimer's disease (Andres-Benito et al, 2018). Heterozygous mutations in Katnip were also recently associated with hypothalamic hamartoma tumours (Fujita et al, 2019).…”
Section: Discussionmentioning
confidence: 86%
“…Viability under starvation was performed based upon (Otto et al, 2003a). Cells were washed twice, resuspended at 5 x 10 5 /mL in SIH -Arg/Lys and maintained in shaking flasks.…”
Section: Cell Culturementioning
confidence: 99%
“…The endocrine feature is also common in other ciliopathies such as JS and JSRD. Some JS/JSRD patients show growth hormone or thyroid hormone deficiency [ 127 ], CPHD [ 128 ], and micropenis [ 129 ].…”
Section: Wdr Proteins In Human Diseasementioning
confidence: 99%